WATER QUALITY AND VERTICAL PROFILE OF KATORI MARU WRECK OFF COAST OF SANTUBONG, SARAWAK - Xinh, Tan Guan (Universiti Malaysia Sarawak(UNIMAS), 2015)
The sunken Japanese cargo ship, Katori Maru is located approximately 30km off the coast of Santubong was sunk by the damage receive from the torpedo shot by Dutch submarine K-XIV during Christmas Eve 1941 during World War II. After several decades in the bottom of the seabed, Mother Nature has engulfed the sunken ship and transform to a living museum and an ecosystem for marine flora and fauna. Despite being a famous diving spot, no study has been documented. Hence this studies aim to document the water quality and the vertical profile of the Japanese shipwreck, Katori Maru. Standard method APHA is used to study the water quality and CTD casting is used to determine the vertical profiles. It is shows that the wreck act as an source of nutrient, iron to increase biological productivity, thus give a good productivity, and high dissolved oxygen in the water column as compare along the transect from wreck PMSC jetty. Chlorophyll a concentration ranged from 0.16μg/L, 0.19μg/L, and 0.10μg/L in surface, mid depth and bottom respectively. The presence of wreck cause localize upwelling in the water column indicate by TSS, range from surface to bottom is 20mg/L, 30mg/L and 30mg/L.